2008
DOI: 10.1038/pcan.2008.29
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic lymphadenectomy in prostate cancer

Abstract: This review analyzes the anatomy of the prostate gland's lymphatic drainage, the optimal anatomic extend of pelvic lymph node dissection (PLND) and which dissection may be superior, who should undergo a PLND during prostatectomy, and its potential therapeutic benefits and complications. The prostate gland's lymphatic drainage can be variable, but frequently metastatic disease is found in the internal iliac chain. We conclude that the extended PLND yields the most lymph nodes and therefore may be superior. Some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 57 publications
0
23
0
1
Order By: Relevance
“…39 This can be performed with wide-bandwidth cameras and laparoscopic cameras during robotic-assisted surgery. 40 The goal of the approach is to reduce operative time, improve diagnostic accuracy, and decrease morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…39 This can be performed with wide-bandwidth cameras and laparoscopic cameras during robotic-assisted surgery. 40 The goal of the approach is to reduce operative time, improve diagnostic accuracy, and decrease morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Although controversies exist regarding the use of a routine bilateral PLND, especially in men with low-and intermediate-risk prostate cancer [1,[14][15][16][17][18][19], PLND remains the most accurate staging procedure for LN invasion [1,20]. Moreover, it has been shown that when PLND is indicated and planned at the time of RRP, this should be extended [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…In literature reviews, the incidence of PCA with nodal involvement ranges between 1.1% and 33.3%, and depends on the median number of removed nodes. [2][3][4][5]15,16 However, the rate of multiple lymph node metastases has rarely been reported and ranges between 4% and 17% of cases. 5 A large multicenter retrospective study has shown that, in high-risk selected patients with at least 10 nodes removed (median 15), the rate of LNI was 36.1%, which included 26.4% of cases having 1 to 3 positive nodes and 9.7% of patients with more than 3 positive lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…9 Although predictors of LNI are well-known form the literature, analysis of factors associated with extensive PLNI are missing. [2][3][4][5][6] The aim of this study was to evaluate clinical predictors of multiple LNI (more than 3 positive nodes) in high-risk PCA.…”
Section: Prostate-specific Antigen Associates With Extensive Lymph Nomentioning
confidence: 99%